Lipoxygenases in chronic liver diseases: current insights and future perspectives. (March 2022) - Heinrich, Lena; Booijink, Richell; Khurana, Amit; Weiskirchen, Ralf; Bansal, Ruchi
Abstract : Chronic liver diseases (CLDs) caused by viral infections, alcohol/drug abuse, or metabolic disorders affect millions of people globally and have increased mortality owing to the lack of approved therapies. Lipoxygenases (LOXs) are a family of multifaceted enzymes that are responsible for the oxidation of polyunsaturated fatty acids (PUFAs) and are implicated in the pathogenesis of multiple disorders including liver diseases. This review describes the three main LOX signaling pathways – 5-, 12-, and 15-LOX – and their involvement in CLDs. We also provide recent insights and future perspectives on LOX-related hepatic pathophysiology, and discuss the potential of LOXs and LOX-derived metabolites as diagnostic biomarkers and therapeutic targets in CLDs. Highlights: Chronic liver diseases (CLDs) are a major cause of mortality and morbidity worldwide that afflict millions of people worldwide and account for 2 million deaths each year. Mammalian lipoxygenases (LOXs) catalyze the biosynthesis of bioactive mediators that are involved in both the progression and regression of various (patho)physiologies. LOXs and their downstream metabolites have been directly and/or indirectly linked to chronic hepatic pathologies including alcoholic and non-alcoholic steatohepatitis. LOXs and their metabolites have emerged as promising biomarkers for diagnosis and staging (including effective management) of different etiological hepatic pathologies. LOX inhibitors, LOX pathway (ant)agonists, specialized proresolving mediators, and their synthetic mimetics have shown great potential in the treatment of liver diseases.